Reactivation of Ni-TiO2 catalysts in hydrogen flow and in supercritical 2-propanol-Comparative study by electron spin resonance in situ - Kandarakova, Irina (Magnetic resonance in chemistry : MRC, 2023)
© 2023 John Wiley & Sons Ltd.